Synthesis and thermal study of 8-hydroxy-quinoline derivatives of the alkaline Earth metals: I. Strontium complexes - Guerreiro, C. T R [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Torres, C. [UNESP] (Springer Nature, 1999)
Strontium complexes of 5,7-dibromo-, 5,7-dichloro-, 7-iodo- and 5-chloro-7-iodo-8-hydroxyquinoline were precipitated from an aqueous ammonia and acetone medium. The complexes obtained were Sr[(C9H4ONBr2)2]·2.5H 2O; Sr[(C9H4ONCl2)(OH)]·1.5H2O; Sr[(C9H5ONI)2]·5H2O and Sr[(C9H4ONICl)(OH)]·1.25H2O. The residues of their thermal decomposition were SrBr2; a mixture of SrCl2, SrCO3 and SrO3 SrCO3, and SrCO3, respectively. All were characterized by means of thermogravimetry, differential thermal analysis, complexometry with EDTA, atomic absorption spectroscopy, IR spectroscopy and X-ray diffraction. © 1999 Akadémiai Kiadó.
Keywords: 8-hydroxyquinoline and its halogenated derivatives; DTA; Strontium; TG; Thermal behaviour; Absorption spectroscopy; Differential thermal analysis; Halogenation; Infrared spectroscopy; Precipitation (chemical); Pyrolysis; Strontium compounds; X ray diffraction analysis; Complexometry; Halogenated derivatives; Hydroxyquinolines; Thermogravimetric analysis